QPSK Vector Millimeter-Wave Signal Generation Based on Odd Times of Frequency Without Precoding - Lun Zhao; Lian Xiong; MingXia Liao; Song Liu; Xiang Yu (IEEE Photonics Journal, 2018)
In this paper, we propose a novel quadrature phase-shift keying (QPSK) vector millimeter-wave (mm-wave) signal generation based on odd times of frequency without precoding. The radio frequency (RF) vector signal generation module is universal for the generation of millimeter-wave signal with any odd frequency multiplication. Instead of phase precoding, the phases of electrical mm-wave signal are multiplied by the frequency multiplication number at the receiver after carrier phase estimation. The frequency tripling, quintupling, and septupling schemes are achieved by simulation, and bit-error-ratio curves demonstrate that the proposed QPSK vector mm-wave signal generation scheme works well.